Investigation of Distribution Characteristics of Cylindrical Particles after the Rupture of Modular Cartridges in a Simulator Chamber - Z. Y. Li; Y. G. Yu; A. Chen (Journal of Applied Fluid Mechanics, 2024)
Modular charging is an advanced technique designed to meet the requirements of auto-loading artillery, whereby granular propellants are stored within modular cartridges that are loaded into the gun chamber. This study employed an extended coupled computational fluid dynamics-discrete element method (CFD-DEM) approach to investigate the gas-particle flow within modular charges. After model validation, we analyzed the distribution characteristics, velocity, coordination number, and orientation of cylindrical pellets in a simulator chamber. Four different loading positions for modular cartridges were examined to assess their impact on particle distribution. Numerical simulations revealed a combination of gentle, horizontal, and steep slopes in the particle distribution. The maximum particle velocity experienced a rapid increase during the initial phase, followed by a zigzag decline after reaching its peak. High-coordination number particles tended to accumulate primarily in the middle layer of steep accumulation. Additionally, the particles exhibited an inverted V-shape orientation range from 0° to 180°, suggesting their tendency to assume upright positions. This established model significantly enhanced our understanding of particle distribution following module cartridge rupture and provided valuable guidance for optimizing the design of large-caliber artillery charges.